Organic–inorganic hybrid nanoflowers: A novel host platform for immobilizing biomolecules - Cui, Jiandong; Jia, Shiru (Coordination chemistry reviews, 2017)
•Organic-inorganic hybrid nanoflowers is still at an early stage of development.•Hybrid nanoflowers are a versatile host platform for the effective biomolecules immobilization systems.•Different approaches and process optimization of preparing hybrid nanoflowers are evaluated.•There will be great demand on biomolecule-inorganic hybrid nanoflowers with diverse functionality. In the past few years, organic–inorganic hybrid nanoflowers technology has been emerged as an effective immobilization method. This method has motivated a considerable interest in exploiting them as a potential matrix for biomolecule immobilization due to their simple synthesis, high efficiency, great promise of enhancing biomolecule stability, activity and even selectivity. Recent years, many efforts have focused on this topic to develop biomolecule-inorganic hybrid nanoflowers with potential applications. In this review, recent advances in functional biomolecule-inorganic hybrid nanoflowers are discussed with an emphasis on the novel synthesizing strategies, process optimization, and their potential applications in biosensor, biocatalysis, drug delivery, and chemical analysis. Trends in current developments toward the rational design of these nanoflowers are identified.